Consumer perception on the sizing provision of selected children wear brands - Navarro, Aryssa Janelle DR., author
Garment sizing plays a significant role in the production of ready-to-wear apparel as it is considered a key factor in providing reasonable garment fit (Tamburrino, 1992; Winks, 1997, as cited in Tongue, Otieno and Cassidy, 2010). Producing garments that will fit all body types is difficult especially for growing children (Tongue et al., 2010). Because of this, the researcher attempted to determine and analyze consumer perceptions on the current sizing provision of selected local children's wear retailers for 2 to 6 year old girls. This is a descriptive study that was conducted in two phases. In Phase I, the sizing provision of selected local children's wear retailers were identified and described through observational store visits. In Phase II, a consumer survey, in online and printed form, was conducted among selected mothers of 2 to 6 year old girls. The researcher used purposive sampling in selecting the three local department stores that were visited, snowball sampling in selecting respondents for the online survey and purposive sampling in selecting survey respondents for the printed survey form. A total of 65 respondents participated in the study. The results of the study showed that the current sizing provision of selected local children's wear retailers does not completely meet the needs of selected consumers with female children between the ages 2 to 6. Though the respondents in this study are generally satisfied with the existing children's sizing systems in the local market, results have shown that more than half of the children in the study do not fit into the clothes designed for their age. A significant number of respondents still encounter fit problems with children's clothing, implying that there is much room for improvement in the aspect of children's sizing standards.